2021
DOI: 10.1016/j.jad.2020.11.117
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health problems during the COVID-19 pandemic: A systematic review and meta-analysis

Abstract: Highlinghts The COVID-19 pandemic increases the prevalence of depression, anxiety, distress, and insomnia. Health care workers and COVID-19 patients are high-risk groups of mental health. Urgent interventions are needed for preventing mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

60
812
19
45

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 948 publications
(936 citation statements)
references
References 51 publications
60
812
19
45
Order By: Relevance
“… 19 Pre-existing health conditions, high estimates of personal risk and time spent quarantining, all of which are more prevalent in those aged ≥ 70 years, appear to be independent risk factors for depression during the COVID-19 pandemic. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“… 19 Pre-existing health conditions, high estimates of personal risk and time spent quarantining, all of which are more prevalent in those aged ≥ 70 years, appear to be independent risk factors for depression during the COVID-19 pandemic. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the association between social distancing and decreases in symptoms of depression was somewhat unexpected-mostly because studies from several countries have demonstrated that the COVID-19 pandemic has led to considerable increases in symptoms of depression [43][44][45][46][47][48]. However, after conducting an in-depth literature search, participant compliance with COVID-19 precautionary measures may explain the association.…”
Section: Discussionmentioning
confidence: 99%
“…In regards with population subgroups, patients with noninfectious chronic disease (such as cancer or diabetes) had the highest prevalence of depression of all groups, and high rates of anxiety and distress. In addition, people who were quarantined, patients suspected of COVID-19 infection, and physicians and nurses had high prevalence of depression, anxiety, distress and insomnia ( 8 ).…”
Section: Introductionmentioning
confidence: 99%